Predicting effective remifentanil concentration in 95% of patients to prevent emergence cough after laryngomicroscopic surgery - Kim, Ha Yeon (Medicine (Baltimore), 2018)
Smooth emergence or cough prevention is a clinically important concern in patients undergoing laryngomicroscopic surgery (LMS). The purpose of this study was to estimate the effective concentration of remifentanil in 95% of patients (EC95) for the prevention of emergence cough after LMS under propofol anesthesia using the biased coin design (BCD) up-down method. A total of 40 adult patients scheduled to undergo elective LMS were enrolled. Anesthesia induction and maintenance were performed with target-controlled infusion of propofol and remifentanil. Effective effect-site concentration (Ce) of remifentanil in 95% of patients for preventing emergence cough was estimated using a BCD method (starting from 1 ng/mL with a step size of 0.4 ng/mL). Hemodynamic and recovery profiles were observed after anesthesia. According to the study protocol, 20 patients were allocated to receive remifentanil Ce of 3.0 ng/mL, and 20 patients were assigned to receive lower concentrations of remifentanil, from 1.0 to 2.6 ng/mL. Based on isotonic regression with a bootstrapping method, EC95 (95% CI) of remifentanil Ce for the prevention of emergence cough from LMS was found to be 2.92 ng/mL (2.72–2.97 ng/mL). Compared with patients receiving lower concentrations of remifentanil, the incidence of hypoventilation before extubation and extubation time were significantly higher in those receiving remifentanil Ce of 3.0 ng/mL. However, hypoventilation incidence after extubation and staying time in the recovery room were comparable between the 2 groups. Using a BCD method, the EC95 of remifentanil Ce for the prevention of emergence cough was estimated to be 2.92 ng/mL (95% CI: 2.72–2.97 ng/mL) after LMS under propofol anesthesia.